2018
DOI: 10.1111/1471-0528.15403
|View full text |Cite
|
Sign up to set email alerts
|

Asparaginase‐like protein 1 expression in curettage independently predicts lymph node metastasis in endometrial carcinoma: a multicentre study

Abstract: Low ASRGL1 expression in curettage predicts lymph node metastasis and poor survival in endometrial carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…Notably, PHGDH and ASRGL1 expression were associated with four or more clinicopathologic features ( p < 0.05) (Figure S5F–O), which indicates that PHGDH and ASRGL1 promote the initiation and development of EC. Several studies reported that loss of ASRGL1 is an independent prognostic factor in endometrial cancer 24,25 . PHGDH has been reported to be a potential target in many cancers including breast cancer, 26 colorectal cancer, 27 and melanoma 28 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, PHGDH and ASRGL1 expression were associated with four or more clinicopathologic features ( p < 0.05) (Figure S5F–O), which indicates that PHGDH and ASRGL1 promote the initiation and development of EC. Several studies reported that loss of ASRGL1 is an independent prognostic factor in endometrial cancer 24,25 . PHGDH has been reported to be a potential target in many cancers including breast cancer, 26 colorectal cancer, 27 and melanoma 28 .…”
Section: Resultsmentioning
confidence: 99%
“…ASRGL, has been reported to promote cell proliferation and suppress apoptosis in various tumors, including breast, ovarian, cervical, and EC 46 . In EC, it is shown to be a reliable negative prognostic biomarker that is related to overall survival, lymph‐node metastasis, and aggressive clinicopathologic features 24,25 . Interestingly, studies indicate the relationship of ASRGL1 expression with hormone receptor status, 46 which builds a link between glutamine and amino acid metabolism with hormone homeostasis, as EC is hormone‐dependent tumor.…”
Section: Discussionmentioning
confidence: 99%
“…AKR1B10 encodes a member of the aldo–keto reductase (AKR) 1B subfamily and exerts variable or even opposing roles in different tumor contexts [ 28 , 29 ]. ASRGL1 encodes the enzyme that catalyzes the hydrolysis of l -asparagine to l -aspartic acid and ammonia and plays a protective role in endometrial carcinoma [ 30 ]. ABCC2, ATP Binding Cassette Subfamily C Member 2, acts as a key transporter in support of cell energy transition and proliferation and was identified as a pro-oncogenic factor in colorectal cancer [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the high-risk IW4 group had worse outcome and a higher prevalence of LNM (53%), compared to the high-risk ESMO group (17%). [11,32,33], and a few have also incorporated preoperative imaging findings [34][35][36][37][38]. Reijnen et al have presented a Bayesian network (ENDORISK) that includes molecular and clinical biomarkers, including lymphadenopathy on imaging, yielding AUCs of 0.82-0.84 for predicting LNM [38].…”
Section: Discussionmentioning
confidence: 99%